Chronic suppurative otitis media - Morris, Peter (BMJ Publishing Group, 2012)
INTRODUCTION: Chronic suppurative otitis media (CSOM) is a common cause of hearing impairment and disability. Occasionally it can lead to fatal intracranial infections and acute mastoiditis, especially in developing countries. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical questions: What are the effects of treatments for chronic suppurative otitis media in adults and in children? What are the effects of treatments for cholesteatoma in adults and in children? We searched: Medline, Embase, The Cochrane Library, and other important databases up to May 2010 (Clinical Evidence reviews are updated periodically, please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 51 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review, we present information relating to the effectiveness and safety of the following interventions: topical ear cleansing, surgery for cholesteatoma, systemic antibiotics, topical antibiotics, topical antibiotics plus topical corticosteroids, topical antiseptics, topical corticosteroids, tympanoplasty (with or without mastoidectomy).